Promotion of Exclusive Breastfeeding through Drinking “Uyup-Uyup” Herbal - Sistiarani, Colti; Wati, Erna Kusuma; Rahardjo, Setiyowati (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Tradition mother after delivery baby ussually drinks uyup-uyup herbal. Uyup-uyup herbal is believed to smooth milk, so many mothers do traditional drink called uyup-uyup herbal in the postpartum period. This study aims treatment role of herbalist to be agents of change in promoting exclusive breastfeeding. This study intervension train uyup-uyup herbalist. Uyup-uyup herbalist who have been trained and then required to practice the promotion of exclusive breastfeeding to lactating mothers. Quantitative study used quasi-experimental research design to determine the effect of treatment exclusive breastfeeding promotion. The treatment group was located in the Bojongsari District and the control group in the Padamara district. The number of samples the treatment group and the control group respectively by 40 lactation mothers The results showed the differences knowledge and attitudes about exclusive breastfeeding in the treatment group. From these results exclusive breastfeeding promotion efforts can be done through intermediaries uyup-uyup herbalist to mothers.